Rectifier Design Challenges for RF Wireless Power Transfer and Energy Harvesting Systems - A. Collado (Radioengineering, 2017)
The design of wireless power transfer (WPT) and energy harvesting (EH) solutions poses different challenges towards achieving maximum RF-DC conversion efficiency in these systems. This paper covers several selected challenges when developing WPT and electromagnetic EH solutions, such as the design of multiband and broadband rectifiers, the minimization of the effect that load and input power variations may have on the system performance and finally the most optimum power combining mechanisms that can be used when dealing with multi-element rectifiers.